AN EXPLORATORY INVESTIGATION ON PROJECT ASSESSMENT OF STUDENTS’ SPEAKING SKILLS IN PROJECT-BASED LEARNING (PBL) - Widya Rizky Pratiwi (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2017)
This article attempts to present the way to increase students’ speaking skill through project assessment in Project-Based Learning (PBL) approach. This article was explored in qualitative design using descriptive method to find out how the project assessment runs and functions and find out the students’ perception of project assessment. Assessment is an activity to answers the question of what is the result such as what is being learned by the students, what is the impact being made by instruction, what is working, what is not working, what can students do and what is the faculty accomplishing. And then, it measures the students’ achievement that can cover three aspects of learning namely cognitive, affective and psychomotoric. Project assessment in Project Based Learning is offered to increase the students’ speaking skill because it is an assessment of assignment that must be completed by students in particular period of time. The assignment is contextualizes learning by investigation form beginning from collecting, organizing, evaluating, until presenting the data with problems to be solved or products to be developed.